Epidemiology and clinical outcomes of viral central nervous system infections. (August 2018) - Ben Abid, Fatma; Abukhattab, Mohammed; Ghazouani, Hafedh; Khalil, Obada; Gohar, Ahmed; Al Soub, Hussam; Al Maslamani, Muna; Al Khal, Abdullatif; Al Masalamani, Eman; Al Dhahry, Said; Hashim, Samar; Howadi, Faraj; et al.
Highlights: Among 7690 patients with available CSF results, 550 cases met the inclusion criteria (meningitis 75%; encephalitis 25%). Viral etiology was confirmed in 38% (enterovirus, 44%; Epstein-Barr virus, 31%; varicella zoster virus, 12%). Our results showed that EBV was the leading pathogen among cases of encephalitis. We could not find other associated causative pathogens or underlying comorbidities in our patients. The climate and heterogeneity of our population might be the explanation of this new trend. Antibiotics and acyclovir are overly used even when a viral etiology is confirmed. There is a need for clinician education regarding etiology and treatment of viral CNS infections. This will have further implications on antimicrobial stewardship to prevent unnecessary use of antibiotics and antivirals and consequently prevent further resistance. Abstract: Background: Central nervous system (CNS) viral infections are an important cause of morbidity and mortality. No data are available regarding their epidemiology in Qatar. Design: We retrospectively evaluated all cerebrospinal fluid findings from January 2011–March 2015 at Hamad Medical Corporation. Those with abnormal CSF finding were included in our study. We excluded those with missing medical records, no clinical evidence of viral CNS infection, or proven bacterial, fungal or tuberculosis CNS infection. CNS clinical findings were classified as meningitis, encephalitis or myelitis. Results: Among 7690 patients with available CSF results, 550 cases met the inclusion criteria (meningitis 74.7%; encephalitis 25%; myelitis 0.4%). Two-thirds (65%) were male and 50% were between 16–60 years old. Viral etiology was confirmed in 38% (enterovirus, 44.3%; Epstein-Barr virus, 31%; varicella zoster virus, 12.4%). The estimated incidence was 6.4 per 100, 000 population. Two persons died and the rest were discharged to home. Among those with confirmed viral etiology, 83.8% received ceftriaxone (mean duration 7.3 ± 5.2 days), 38% received vancomycin (mean duration 2.7 ± 5.4 days) and 38% received at least one other antibiotic. Intravenous acyclovir was continued for more than 48 h in patients with confirmed negative viral etiology (mean duration 5 ± 5.6 days). Conclusion: Viral etiology is not uncommon among those evaluated for CNS infection in Qatar. Clinical outcomes are excellent in this group of patients. Antibiotics and acyclovir are overly used even when a viral etiology is confirmed. There is a need for clinician education regarding etiology and treatment of viral CNS infections.